Evaluate the Impact of a Structured Educational Program on Postnatal Mothers’ Understanding of Kangaroo Mother Care in a Tertiary Care Hospital - Anagha K. Saji; M.N. Pavithra; V. Divya Sri (International Journal of Midwifery Nursing And Practices, 2024)
Background and Aims:Kangaroo mother care (KMC) is an innovative method for caring for low-birth-weight infants. The main goal of this study is to evaluate the effectiveness of a structured teaching program in enhancing knowledge about KMC among postnatal mothers admitted at a tertiary care hospital. Material and Methods: Pre-experimental one-group pre-test and post-test designs were used and selected 80 postnatal mothers who met the inclusion criteria the experimental group received a structured teaching program on KMC for 45 minutes. Results: The analysis of post-test knowledge scores among postnatal mothers revealed significant differences. Comparing the mean scores and standard deviations, the post-test mean score was 40.09 with a standard deviation of 19.8, while the pre-test mean was 25.1 with a standard deviation of 12.43. The calculated “t” value of 2.02 was significant at a p-value of 0.023. These findings indicate that the structured teaching program on KMC was effective in enhancing knowledge among postnatal mothers. Conclusion: The study aimed to evaluate how well a structured teaching program improved postnatal mothers’ understanding of KMC. After the program, post-test results showed higher overall percentage and mean knowledge scores compared to the pre-test. This suggests that the structured teaching program effectively enhanced knowledge about KMC among the participants.
Keywords: Kangaroo mother; postnatal mother; qualitative research